KOMIZM I JEGO ŹRÓDŁA W PIŚMIE „DE VITANDO AERE ALIENO” PLUTARCHA Z CHERONEI - Osiński , Piotr (Studia Europaea Gnesnensia, 2018)
This paper is devoted to the humour in Plutarch’s speech De Vitando Aere Alieno (That One Ought Not to Borrow). Although the problem raised in this work appears to be serious, Plutarch included humorous elements. Among the ancient Greeks and Romans, not only was usury a grave issue, but also one which gave rise to humour. Plutarch used the tradition of comedy and Cynic-Stoic diatribe in a rhetorical purpose. His aim was to persuade the listener or the reader to adopt a moral attitude towards usury.